2019
DOI: 10.37236/7239
|View full text |Cite
|
Sign up to set email alerts
|

Monochromatic Cycle Partitions of $2$-Coloured Graphs with Minimum Degree $3n/4$

Abstract: Balogh, Barát, Gerbner, Gyárfás, and Sárközy proposed the following conjecture. Let G be a graph on n vertices with minimum degree at least 3n/4. Then for every 2-edge-colouring of G, the vertex set V (G) may be partitioned into two vertex-disjoint cycles, one of each colour.We prove that this conjecture holds for n large enough, improving approximate results by the aforementioned authors and by DeBiasio and Nelsen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…Furthermore, Example 3.3 shows that this is best possible if true. Regarding the distinct colors variant of these problems, we make the following conjecture which is true for r = 1 as above, and for r = 2 by Letzter's result [26]. Furthermore, Example 3.5 shows that this is best possible if true.…”
Section: Open Problemsmentioning
confidence: 75%
See 1 more Smart Citation
“…Furthermore, Example 3.3 shows that this is best possible if true. Regarding the distinct colors variant of these problems, we make the following conjecture which is true for r = 1 as above, and for r = 2 by Letzter's result [26]. Furthermore, Example 3.5 shows that this is best possible if true.…”
Section: Open Problemsmentioning
confidence: 75%
“…That is, if δ(G) > 3n/4, then cp 2 (G) ≤ 2 (with cycles of different colors); they also provided an example which shows that the conjecture would be best possible. DeBiasio and Nelsen [8] proved that this holds for G with δ(G) > (3/4 + o(1))n and then Letzter [26] proved that it holds exactly for sufficiently large n.…”
Section: Large Minimum Degreementioning
confidence: 96%
“…Some generalizations of these results concerning more complicated graphs other than paths or cycles were obtained in [8,21]. Similar properties of host graphs other than complete graphs were also studied: complete bipartite graphs are considered in [9,13,17], complete graphs with only few edges missing in [11], graphs with large minimum degree in [2,5,18] and graphs with small independence number in [20]. For further results and research directions we refer the reader to the recent survey by Gyárfás [10].…”
mentioning
confidence: 86%
“…Most of the difficulty is in the proof for r = 3, but we include a short proof for r = 2 for completeness. Actually, the r = 2 case (for n large) already follows from a difficult result of Letzter [14], who showed that when ≥ ∕ δ G n ( ) 3 4, the vertices can be partitioned into two monochromatic cycles of different colors, for every 2-coloring of G. Before turning to the proofs, we mention the following construction of Bal and DeBiasio [3], which shows that the minimum degree condition in Conjecture 1.5 cannot be improved. F I G U R E 1 An illustration of Example 3.1 for t = 2 and t = 3 (here gray represents red and black represents blue) 2 In fact, we need to be a bit more careful here.…”
Section: Of Distinct Colorsmentioning
confidence: 99%